Facial approximations: Characteristics of the eye in a South African sample. (May 2018) - Dorfling, Heléne F.; Lockhat, Zarina; Pretorius, Samantha; Steyn, Maryna; Oettlé, Anna C.
Highlights: Dimensions of the eye and orbit in South Africans varies from published guidelines. A more rectangular orbit results in a more transversely elongated eyeball. The eyeball is located 13.2 mm superiorly and 14.6 mm laterally from orbit centre. The exocanthion is situated lower than the endocanthion. Abstract: Although guidelines for facial approximations, including those for the eye, are in use in South Africa, limited data on African populations exist to confirm its validity. As precise placement of the eyes in facial approximations is of importance for facial recognition, this study tested established guidelines by measuring specific instrumental dimensions. Forty-nine cadavers from the Sefako Makgatho Health Sciences University and the University of Pretoria were dissected to determine the position of the canthi and the size and position of the eyeball in the orbit. Thirty cone beam computer tomography scans and 30 computer tomography scans from the Oral and Dental and Steve Biko Hospitals respectively were used to determine the size of the eyeball. Results from this study were compared to the published guidelines. The most prominent discrepancies included a more rectangular shape of the orbit, an oval shaped eyeball and a different position of the canthi. In African faces, the medial canthus was found to be located higher than the lateral canthus. The distance between the endocanthion and superior orbital margin was 17.7 mm and the exocanthion and superior orbital margin 19.5 mm. Inter-population differences may have an effect on facial approximations and its accuracy as is often demonstrated in practice. The findings of this study should be taken into consideration when designing population specific guidelines for reconstruction of the eye in South Africans of African ancestry.